Gone in the blink of an eye – A Tolosa-Hunt syndrome variant. (February 2020) - Dholoo, Farzan; Shabana, Amanda; Paschali, Myrella; Mandal, Amit K.J.; Missouris, Constantinos G
Highlights: The Tolosa-Hunt syndrome (THS) is characterised by painful ophthalmoplegia. THS results from compression of structures within the cavernous sinus by pseudotumour. Its diagnosis can only be made if the potentially fatal processes within the differential have been adequately excluded. Resolution of orbital pain within 1–3 days of treatment with corticosteroids also serves as diagnostic affirmation. THS variant may present as painless ophthalmoplegia, which may be a self-limiting process. Abstract: Tolosa-Hunt syndrome is a rare disorder characterized by severe peri-orbital headache and ophthalmoplegia resulting from pseudotumour in the cavernous sinus compressing structures within it, namely cranial nerves III, IV, and VI and the superior divisions of cranial nerve V. We report the case of a 47 year old female who presented with painless left unilateral ptosis and complete external ophthalmoplegia. Magnetic Resonance Imaging (MRI) identified an enhancing heterogeneous mass filling the left cavernous sinus, following the course of the oculomotor nerve. After 2 weeks symptoms and signs resolved and there was a parallel resolution of the MRI findings, without the administration of corticosteroids. As far as we are aware this is one of the first reports of Tolosa-Hunt syndrome variant, with painless neurological involvement confined solely to the oculomotor nerve, and with complete resolution without pharmacological intervention.